Development of the Snake and Leader Game Model to Improve Physical Motor in Early Childhood - Marwan, Iis; Wahidah, Ida; Rohayati, Nia (Journal of SPORT (Sport, Physical Education, Organization, Recreation, and Training), 2024)
It is very important to pay attention to motor development in early childhood, this will affect the child's motor skills as an adult. Improving movement abilities in early childhood can be done with game models that suit the characteristics of early childhood. The game model that will be developed in this research is a movement game using snake and ladder. The method used in this research is research development from Borg and Gall (1989). The research will go through ten stages from the researcher collecting problems that will become research topics to large-scale production. This research also went through the stages of testing the game model and was given validation. During the trial, the effectiveness of this snake and ladder game model will also be seen. After being developed, this snake and ladder game model includes jumping movements with one leg or two legs. This research was carried out at Alphabet Kindergarten in Tasikmalaya City. After going through the stages in this development research, it can be concluded that the snake and ladder game model can improve gross motor and fine motor physical abilities in young children.